Patients' perceptions of repair, rehabilitation and recovery after major orthopaedic trauma: a qualitative study. Issue 3 (September 2017) - Claydon, J.H.; Robinson, L.; Aldridge, S.E.
Abstract: Introduction: The most common major trauma injuries are multiple fractures. Orthopaedic trauma research has traditionally focused on surgical techniques, and the impact of this major life event on the patient is not well understood. This study explored how patients make sense of their rehabilitation and recovery following major orthopaedic trauma. Design: Qualitative study using an Interpretative Phenomenological Analysis approach. Methods: Semi-structured interviews of a purposive sample of 15 patients 3 to 6 months after sustaining major orthopaedic injuries, treated at a major trauma centre in England. Findings: Recovery after trauma was conceptualised as a journey through repair and rehabilitation to achieve recovery. These phases were represented by three superordinate themes: getting back on your feet, getting the right help to get there, and regaining a sense of normality. Participants considered orthopaedic consultants and physiotherapists to be the primary professionals to provide the tools to enable them to help themselves. Improving physical function helped to restore emotional well-being, with recovery only attained when participants had normalised a new sense of self, and regained confidence or enjoyment in their chosen activities. Conclusion: Rehabilitation is a complex process of coming to terms with physical and social limitations to normalise a new sense of self. Individuals considered rehabilitation to be their responsibility; however, they needed expert help to know what to do. Physiotherapists were key to getting people back on their feet, and by facilitating physical recovery, physiotherapists were able to have a positive impact on emotional well-being.